Coronavirus Disease and Abdominal Pain: Mechanism, Diagnostic, and Treatment - Bozhinovska, Aleksandra (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: On March 11, 2020, the General Director of the World Health Organization has announced that according to the organization, the level of spread and severity of symptoms of coronavirus disease (COVID-19) is becoming alarming and because of that, it can be characterized as a pandemic. The assessment of the World Health Organization stimulated more urgent and belligerent actions from the governments as the number of case reports and studies on COVID-19 symptoms and treatment increased dramatically. AIM: In this paper, the aim is to make a review of the studies and case reports/series that indicate that abdominal pain is one of the manifestations of COVID-19. METHODS: A search was performed on two electronic databases: PubMed Central and Google Scholar, using the key words “COVID-19 and abdominal pain.” Case reports and case series in adults and children were included regardless of the language, region, or the publication date. The methods of synthesis and comparison were also used. RESULTS: In general, it can be noted that the manifestation of the COVID-19 infection on the digestive tract and the consequences on the same are not fully examined. CONCLUSION: The conclusion of the analyzed papers is that clinical practitioners in COVID-19 pandemic should carefully distinguish abdominal pain and other GI symptoms from COVID-19 manifestations and should exclude acute surgical condition.